Climate‐change refugia in boreal North America: what, where, and for how long?. Issue 5 (1st June 2020) - Stralberg, Diana; Arseneault, Dominique; Baltzer, Jennifer L; Barber, Quinn E; Bayne, Erin M; Boulanger, Yan; Brown, Carissa D; Cooke, Hilary A; Devito, Kevin; Edwards, Jason; Estevo, César A; Flynn, Nadele; et al.
Abstract : The vast boreal biome plays an important role in the global carbon cycle but is experiencing particularly rapid climate warming, threatening the integrity of valued ecosystems and their component species. We developed a framework and taxonomy to identify climate‐change refugia potential in the North American boreal region, summarizing current knowledge regarding mechanisms, geographic distribution, and landscape indicators. While "terrain‐mediated" refugia will mostly be limited to coastal and mountain regions, the ecological inertia (resistance to external fluctuations) contained in some boreal ecosystems may provide more extensive buffering against climate change, resulting in "ecosystem‐protected" refugia. A notable example is boreal peatlands, which can retain high surface soil moisture and water tables even in the face of drought. Refugia from wildfire are also especially important in the boreal region, which is characterized by active disturbance regimes. Our framework will help identify areas of high refugia potential, and inform ecosystem management and conservation planning in light of climate change.